1994
DOI: 10.2136/sssaj1994.03615995005800020002x
|View full text |Cite
|
Sign up to set email alerts
|

Volatilization of a Multicomponent Liquid through Dry Soils: Testing a Model

Abstract: Spilled or leaked petroleum products often contaminate groundwater and subsequently evaporate through the soil to the atmosphere by gaseous diffusion. This study developed and tested a model that can predict the rate of diffusion through a dry soil column of the individual components in a liquid mixture when they are of low or intermediate volatility. We derived equations that relate the vapor pressures of the components to their sorption from the gaseous phase by the soil. We also provided for slow sorption. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Several studies have specifically evaluated vapor phase sorption/desorption behavior of organic compounds in soils and sediments, [5][6][7][8][9][10][11] including the evaluation of the ultimate distribution of VOCs under equilibrium conditions. Such equilibrium information, in the form of equilibrium isotherms, have been derived using a number of methods including soil column systems, 5,6,[12][13][14][15][16][17][18][19][20][21][22] gravimetric systems 8,9,[23][24][25][26][27][28][29] and headspace methods. 7,[30][31][32][33][34] These methods use equilibrium criteria of minutes to hours, 5,12 one day, 7,29,35 or up to a few days.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have specifically evaluated vapor phase sorption/desorption behavior of organic compounds in soils and sediments, [5][6][7][8][9][10][11] including the evaluation of the ultimate distribution of VOCs under equilibrium conditions. Such equilibrium information, in the form of equilibrium isotherms, have been derived using a number of methods including soil column systems, 5,6,[12][13][14][15][16][17][18][19][20][21][22] gravimetric systems 8,9,[23][24][25][26][27][28][29] and headspace methods. 7,[30][31][32][33][34] These methods use equilibrium criteria of minutes to hours, 5,12 one day, 7,29,35 or up to a few days.…”
Section: Introductionmentioning
confidence: 99%
“…7,[30][31][32][33][34] These methods use equilibrium criteria of minutes to hours, 5,12 one day, 7,29,35 or up to a few days. 22,36 Few researchers have reported long-term sorption data (in excess of a few days) with good mass recoveries, even though it has been shown that some organic contaminants may reside in soils up to 19 years 37 or longer. Reinhard and coworkers 18,19 performed long-term isotherm studies using column systems with equilibration periods of the order of months; however Werth and Reinhard 19 reported sorbate mass recoveries of 88% at 15 °C and 60-85% at 60 °C.…”
Section: Introductionmentioning
confidence: 99%